Outcomes with the Tandem Protek Duo Dual-Lumen Percutaneous Right Ventricular Assist Device. Issue 4 (July 2018) - Ravichandran, Ashwin K.; Baran, David A.; Stelling, Kelly; Cowger, Jennifer A.; Salerno, Christopher T.
Abstract : Recently, a percutaneous right ventricular assist device (RVAD) called the TandemLife Protek Duo (TPD; TandemLife, Pittsburgh, PA) has been introduced. The Protek Duo (TPD) is a temporary RVAD placed via the right internal jugular vein, capable of providing up to 4.5 L of flow. We report a two-center experience using the TPD in 17 patients with right ventricular (RV) failure, 12 of whom were post-left ventricular assist device (LVAD) implantation.